The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1542/peds.2008-1511
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pediatric Monoarticular Arthritis: Distinguishing Lyme Arthritis From Other Etiologies

Abstract: Lyme arthritis shares features with both septic and nonseptic non-Lyme arthritis. This overlap prevents the creation of a clinically useful predictive model for Lyme arthritis. In endemic areas, Lyme testing should be performed on all patients presenting with acute monoarticular arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 19 publications
5
68
0
3
Order By: Relevance
“…All three pointed to a lack of substantially enhanced systemic CRP response in most patients with Lyme arthritis [21][22][23], in agreement with our results. A serum analysis in 20 patients with early neurologic Lyme disease reported a lack of increased CRP concentration in most [24], while a study of 44 Lyme disease patients with EM found both CRP and SAA to be significantly elevated in comparison to 23 healthy controls [25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…All three pointed to a lack of substantially enhanced systemic CRP response in most patients with Lyme arthritis [21][22][23], in agreement with our results. A serum analysis in 20 patients with early neurologic Lyme disease reported a lack of increased CRP concentration in most [24], while a study of 44 Lyme disease patients with EM found both CRP and SAA to be significantly elevated in comparison to 23 healthy controls [25].…”
Section: Discussionsupporting
confidence: 92%
“…non-Lyme arthritis, without incorporating healthy controls [21,22], and one study examined CRP levels in 20 Lyme arthritis patients and 10 healthy volunteers [23]. All three pointed to a lack of substantially enhanced systemic CRP response in most patients with Lyme arthritis [21][22][23], in agreement with our results.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast to septic arthritis, Lyme arthritis is not commonly associated with a hot, erythematous, extremely painful joint, or with high fever. In a recent study of acute monarthritis, fever was a negative predictor for Lyme versus septic arthritis and knee involvement was a positive predictor (Thompson et al, 2009).…”
Section: Clinical Presentationmentioning
confidence: 96%
“…The diagnostic yield of synovial fluid white cell count remains controversial, with a few studies suggesting levels >50,000 cells/μL as a threshold for consideration of septic arthritis [37,38]. However, similar results can also be seen in patients with an acute episode of crystal arthropathy [39][40][41] or acute Lyme arthritis [42].…”
Section: Laboratory Investigationsmentioning
confidence: 99%